Peran Guru dalam Asesmen Kesehatan Mental Anak Usia Dini di Lingkungan PAUD ABA LAMONGAN - Titik Nuryanti; Evita Muslima Isnanda Putri; Siti Patonah (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2024)
Early childhood mental health problems are increasingly receiving attention in various countries, because they have a significant impact on children's future cognitive, social and emotional development. Early childhood is very sensitive to environmental stimulation, both positive and negative (Raver, 2002). Various studies show that mental health disorders in early childhood, such as anxiety, stress, and behavioral problems, can have long-term impacts on children's psychological development, both academically and socially. The aim of this research is to analyze the relationship between the role of teachers and the mental health of early childhood in Early Childhood Education (PAUD) institutions. The method used is a quantitative descriptive method. This research involved 30 PAUD children in Lamongan who were selected using purposive sampling. The instruments used include a Likert scale-based questionnaire to measure the teacher's role, as well as the Strengths and Difficulties Questionnaire (SDQ) to assess children's mental health. The research results show that there is a positive and significant relationship between the role of teachers and children's mental health with a correlation value of 0.425 (p < 0.05), indicating that the active role of teachers in providing emotional support influences children's emotional stability and social skills. In addition, it was found that 66.67% of teachers were effective in supporting children's mental health